A new study of Brazilian concrete strength conformance - Santiago,W.C. (2017)
ABSTRACT This paper presents a new evaluation of the strength compliance of concretes produced in Brazil. It is based on experimental results of over twenty-seven thousand concrete samples from different parts of the country. Results show that a significant part of Brazilian concrete do not reach the characteristic strength (fck) specified in design, and the percentage of nonconforming samples tend to be higher than 5%. This study also reveals the concrete produced in the South and Midwest regions have less variability than the ones produced in the other regions of the country. These results emphasize the importance of a rigorous control in manufacturing and reception of concretes in order to reduce the nonconforming cases.